KEBIJAKAN SISTEM ZONASI DALAM PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 1 TAHUN 2021 TENTANG PENERIMAAN PESERTA DIDIK BARU PADA TAMAN KANAK-KANAK, SEKOLAH DASAR, SEKOLAH MENENGAH PERTAMA, SEKOLAH MENENGAH ATAS, DAN SEKOLAH MENENGAH KEJURUAN - Pangiestu, Adjie; Indra, Mexsasai; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The implementation of the zoning system in the admission of new studentsraises various problems. The zoning system is regulated by the Ministry ofEducation and Culture of the Republic of Indonesia in the Regulation of theMinister of Education and Culture of the Republic of Indonesia Number 1 of 2021concerning Admission of New Learners in Kindergartens, Elementary Schools,Junior High Schools, Senior High Schools, and Vocational High Schools, while inArticle 51 paragraph (1) of Law Number 20 of 2003 concerning the NationalEducation System it is stated that schools are given autonomy to manage theirschools. This autonomous right to schools is in the form of School-BasedManagement principles to organize and manage their own education.This thesis uses research with a type of normative research, namelylibrary research. In this research, the data sources used are secondary datasources with primary legal materials of the Minister of Education RegulationNumber 1 of 2021 with Law Number 20 of 2003. The collection technique usesdocumentation / literature study, namely analyzing and examining these primarylegal materials.Minister of Education and Culture Regulation Number 1 of 2021 and LawNumber 20 of 2003 are considered to be out of sync. The incompatibility andinconsistency of these regulations have caused various social and moral problemsthat affect various elements, especially prospective students and theirparents/guardians. The zoning system policy implemented in the New LearnerAdmission results in some people who want to impose their will because they havecertain perceptions, resulting in actions that are against the law, morals, social,and religion. The purpose of the zoning system is very good to advance educationin Indonesia, but many aspects have not been fulfilled by the Government inimplementing this zoning system. Such as unequal access to education inIndonesia, inequality of facilities and infrastructure in various schools, to theuneven quality of teachers in each region.Keywords: Zoning System and New Student Admission